2012
DOI: 10.1186/1471-2091-13-24
|View full text |Cite
|
Sign up to set email alerts
|

A standard numbering scheme for thiamine diphosphate-dependent decarboxylases

Abstract: BackgroundStandard numbering schemes for families of homologous proteins allow for the unambiguous identification of functionally and structurally relevant residues, to communicate results on mutations, and to systematically analyse sequence-function relationships in protein families. Standard numbering schemes have been successfully implemented for several protein families, including lactamases and antibodies, whereas a numbering scheme for the structural family of thiamine-diphosphate (ThDP) -dependent decar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 54 publications
1
63
0
Order By: Relevance
“…A standard numbering scheme was established for Classical and Extended SDRs to facilitate the identification of structurally and functionally equivalent positions, as it had been previously shown for other enzyme families . Crystal structures were selected to cover mostly all homologous families of Classical and Extended SDRs in the SDRED with known PDB entries.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A standard numbering scheme was established for Classical and Extended SDRs to facilitate the identification of structurally and functionally equivalent positions, as it had been previously shown for other enzyme families . Crystal structures were selected to cover mostly all homologous families of Classical and Extended SDRs in the SDRED with known PDB entries.…”
Section: Methodsmentioning
confidence: 99%
“…Protein family databases are useful tools to study the relationship between sequence, structure, and function of enzymes and to support the design of novel enzymes . In this study, the Short‐chain Dehydrogenase/Reductase Engineering Database ( https://sdred.biocatnet.de/ .)…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a numbering scheme for all decarboxylases was developed that assigns an identical number to each equivalent position in all members of the superfamily. [33] As a consequence, the residues of the S-pocket of the decarboxylases PfBAL, PpBFD, ApPDC, EcMenD, and EcAHAS II have the same standard number 477, although the respective amino acids and their numbers in the respective protein sequences differ (T481, L461, E469, F475, and V461, respectively). A profile-hidden Markov model was created by using a set of representative decarboxylases, including the pyruvate decarboxylase from S. cerevisiae as a reference sequence.…”
Section: Case Study 1: Engineering the Regioselectivity Of Cytochromementioning
confidence: 99%
“…Upon aligning each decarboxylase sequence to the profile, the absolute residue numbering of the reference sequence was transferred to all members of the decarboxylase protein family. [33] By systematically comparing the sequences and structures of all decarboxylases, two hotspot positions were identified that mediate binding of the acceptor molecule: position 477 (standard numbering), which determines the size of the Spocket, and position 476, which might block the entrance to the S-pocket ( Table 1). …”
Section: Case Study 1: Engineering the Regioselectivity Of Cytochromementioning
confidence: 99%
“…On the other hand, the structural similarity of ThDP‐dependent decarboxylases, for instance, is not reflected at sequence level and even in the catalytic domains only comparably few positions are conserved . To facilitate the identification of functionally relevant amino acid positions in related enzymes, a standard numbering scheme was established for ThDP‐dependent decarboxylases using a profile hidden Markov model (HMM) derived from a structure‐guided multiple sequence alignment of representative sequences . The pyruvate decarboxylase from Saccharomyces cerevisiae (PDB accession 2VK8) was chosen as a reference for sequence numbering .…”
Section: Introductionmentioning
confidence: 99%